Lower esophageal sphincter achalasia-like syndrome causing megaesophagus in a cat - Carol Reinero; Megan Grobman; Aida Vientós-Plotts; Isabelle Masseau; Charlotte Gerhard (Journal of Feline Medicine and Surgery Open Reports, 2025)
Case summary Feline megaesophagus (ME) is a rare failure of esophageal motility leading to regurgitation, weight loss and sometimes death in cats. It has been identified secondarily to neurologic and neuromuscular disorders, mechanical obstruction of the esophagus (eg, vascular ring anomalies, esophageal stricture) and upper airway obstruction among others; when no cause is found, it is considered idiopathic. Videofluoroscopic swallow studies (VFSSs), especially using an unrestrained free-feeding protocol, are underutilized for comprehensive evaluation of cats with regurgitation, including identifying the etiology of ME. In this case report, a 3-month-old male intact domestic shorthair cat with a history of regurgitation since weaning and radiographic evidence of ME had VFSS features compatible with a functional obstruction of the lower esophageal sphincter (LES) consistent with LES achalasia-like syndrome. Medical management with sildenafil failed to improve clinical signs, and surgical correction of LES achalasia using a Heller myotomy and Dor fundoplication was declined. As a result of caregiver compassion fatigue from persistent regurgitation, euthanasia was elected. Relevance and novel information Videofluoroscopic documentation of functional obstruction of the LES (ie, LES achalasia-like syndrome) can identify a novel etiology of feline ME. Free-feeding unrestrained VFSS protocols are recommended to allow physiologic assessment of swallowing disorders with no higher risk of aspiration than eating and drinking at home. Recognition of LES achalasia-like syndrome may lead to further study of directed treatments targeting the functional obstruction as has been carried out in humans and dogs.